Efforts of the Samapta Unit’s Two-Wheeled Motorcycle Patrol to Prevent Curanmor in the Lamongan Police Station - Argyapratama, Naufal (Indonesian Journal of Police Studies, 2024)
Crime is a real problem in people’s lives. Since crime is a global problem, it can occur anywhere in the world. Today, crime has developed into a frequent phenomenon, crime will inevitably occur in society with different interests. Based on data from the Lamongan Police in table 1.1, it can be concluded that from the vulnerable time of 2019 to 2022, the crime of theft of motorized vehicles has increased and has experienced a drastic increase almost doubling in 2021 to 2022, therefore a police action is needed to prevent crimes that disrupt public security and order (maintenance of public security and order).The method used in this research is Field Research, which is a research method by looking directly at conditions in the field so that it is expected to understand the problem deeply and completely. Field Research combines observation techniques with open interviews, as well as examination and data collection if needed. This means that after watching the Subject (the person being observed) perform an activity or behave / behave subject. Researchers directly interview so that they can understand the reasons and factors behind the two-wheeled patrols that have been carried out by the police.The two-wheeled patrol that has been carried out by the Lamongan Police Samapta Unit, of course, there must be factors that hinder it. There are internal factors and external factors. Internal factors in the form of low motivation of members to carry out patrols. In addition, the leadership’s concern for members must be increased. External factors in the form of rainy weather conditions can hinder patrol activities, plus slippery road conditions and trees that are prone to falling can be an obstacle. The researcher will analyze these factors using George Robert Terry’s management theory known as The 6 M.